Faktor Internal Individu dan Delinkuensi: Kajian ke atas Remaja Perempuan di Asrama Akhlak Perempuan, Jitra (Jurnal Pembangunan Sosial, 2015)
Statistic reported that the involvement of female teenagers in delinquency behavior is increasing. According to the literature, one of the aspects that contribute to delinquency among female teenagers is individual internal factor. Thus, this study is aimed to analyze the internal aspects of female teenagers who are involved in delinquency behavior. The study applied qualitative approach. Respondents were selected by purposive sampling technique. Data was gathered through an in-depth interview with the respondents. Information from the interview was recorded to ensure that the information is completed. The data from the recorder was then transferred into a writing format manually. The data was analyzed to obtain the study themes. Results of the study showed that there are three internal aspects that influence the respondents to involve in delinquency such as perception towards their delinquency acts, life experiences and their reaction towards any particular situations.